Taxonomic revision of Neodiogmites Carrera, 1949 (Diptera, Asilidae) and description of two new species - Alvim, Edgar; Ale-Rocha, Rosaly; Bravo, Freddy (Zootaxa, 2014)
Neodiogmites Carrera, 1949, a rare Neotropical genus of Asilidae, is revised and divided into three species groups: (1) the melanogaster group, including N. carrerai Artigas & Papavero, N. melanogaster (Wiedemann, 1821), N. tenebrosus Carrera and N. carolindae sp. nov.; (2) the alexanderi group, including N. atriapex (Carrera & Papavero), N. alexanderi (Carrera), N. mixtus (Carrera), N. modestus (Carrera) reval., N. niger (Carrera) and N. papaveroi sp. nov.; and (3) the lanei group including N. lanei (Carrera) and N. tauauna Artigas & Papavero. A key to the 12 species is included, species distributions are summarized, and two new species are described and illustrated.